AN APPRAISAL ON DHARANIYA VEGAS IN CHARAKA SAMHITA - KOTEKAR, AJANTHA SHIVAJI; S, Geetha nayak; M K, Anjana; S, Anand (Asian Journal of Pharmaceutical Research and Development, 2018)
Basic principles of Ayurveda emphasize the importance of hetu (causative factor) in disease pathogenesis. Indulgence in dharaniya vega (urges to be suppressed or controlled) acts as a factor in cascade of pathogenesis. In Charaka Samhita description on nine dharaniya vegas is scattered in different contexts. Collection of all these information and analysis paves way for better understanding of the concept of Dharaniya vegas and very helpful in health promotion. It is quite interesting to note that these dharaniya vegas are connected to emotional states of mind. The natural urges of mind are important aspect of living body and significantly determine the health or diseased state of an individual. Individual desirous of health should control these urges by gaining control over sense organs. These nine dharaniya vegas, if not controlled can lead to tridosha prakopa (vitiation of body humours) and result in varied psychosomatic manifestations. In the present article an attempt is been made to explore the concept of dharaniya vega mentioned in Charaka samhita with contemporary relevance in clinical Ayurveda practice and thereby aide in health promotion and also as a preventive tool. Key words: